Analisis Ekonomi dan Finansial Kereta Cepat Jakarta - Bandung - Giantara, Oldebes Temy; Purba, Aleksander; Herianto, Dwi (Universitas Lampung, 2018)
Jakarta and Bandung city with a distance about 150 km must be taken more than three hours by highway or railway due to the ever-increasing mobility with limited infrastructure capacity. This study analyzes the economic and financial feasibility of the Jakarta – Bandung high speed rail project and calculates the NPV, BCR, IRR, PI, and PP. The government through the SOE and China International Railway consortium initiated the construction of a high speed rail from Halim to Tegalluar with a 142,3 km rail length and an average speed of 250 km/h, construction began in 2015 and is expected to be completed by 2020. The analysis is done with assumption of 75% occupancy rate, with discount rate of 2% and 3,46%, and feasibility of the project by doing comparison of feasibility method that is NPV ≥ 0, BCR > 1, IRR > r, PI > 1, and PP is faster than NPV positive. In the highest value feasibility analysis obtained with 75% occupancy rate and discount rate 2%. If only calculate the economic benefits obtained value of NPV = 3.279.703.704,18 ≥ 0, BCR = 1,00 > 1, IRR = 6,45% > r, PI = 0,65 < 1, PP = 33,76 > 29 year. If only calculate the financial benefits obtained value of NPV = 8.677.268.827,83 ≥ 0, BCR = 1,01 > 1, IRR = 5,50% > r, PI = 0,79 < 1, PP = 34,47 < 38 year. If calculate the economic and financial benefits obtained value of NPV = 1.543.396.683.112,40 ≥ 0, BCR = 1,56 > 1, IRR = 105,46% > r, PI and PP can not be calculated because the positive value of NPV in the first year (2020).